From The History Of The Fergana Economic Region - Yusupova Gullola Tuhtamurodovna (International Scientific and Current Research Conferences, 2020)
The Fergana economic region, which has a place not only in the Central Asian economic region, but also in the economic life of the whole country, has become a region that provides the country with light industry, food and chemical products. In addition to the availability of a variety of natural resources in this economic region, cotton, silkworm, and fruit growing are very well developed. The article analyzes the structure of the Fergana economic region and its role in the national economy.